Doped-Ceria Electrolytes Synthesis, Sintering and Characterization - Spiridigliozzi, Luca.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book provides an overview of fuel cell technology and, in particular, of Solid Oxide Electrolysis Cells (SOFCs). Each chapter highlights the effects of different synthesis parameters and/or adopted sintering method, clarifying both advantages and disadvantages pointed out by different experimental campaigns. The book focuses on Doped-Ceria Electrolytes, presenting an engineered production process of GDC/SDC electrolytes by using a combination of wet chemical synthesis and/or alternative sintering techniques, capable of enhancing electrolytes microstructural features and electrical properties at reduced temperature and time. The author proposes useful guidelines to produce dense and high-preforming ceria-based electrolytes for IT-SOFCs.
Keywords: Ceramic materials; Materials; Catalysis; Force and energy; Ceramics; Materials for Energy and Catalysis; Materials Engineering